MODEL FOR THE DEVELOPMENT OF COGNITIVE COMPETENCE OF BACHELORS IN THE SUBJECT METHODOLOGY OF TEACHING MATHEMATICS - Zahrooy Tokhirova (Bright Mind Publishing, 2025)
This article explores the theoretical foundations and practical approaches to developing cognitive competence among undergraduate students in the course “Methods of Teaching Mathematics.” It emphasizes the effectiveness of non-standard tasks developed using the iSpring Quiz platform in enhancing students' skills in logical reasoning, independent thinking, and problem-solving. The paper also analyzes heuristic problems, the case study method, and techniques for assessing cognitive competence.
Keywords: Cognitive competence, methods of teaching mathematics, non-standard tests, iSpring Quiz, heuristic problems, case study, educational technologies.